Transfer Pricing Rules for Intangibles: Implementation and Practical Challenges - Safaei, Reyhaneh

Changes in Transfer Pricing Regulations and Corporate Investment Decisions - Shabestari, Mehrzad Azmi; Safaei, Reyhaneh

Are Risk-based Tax Audit Strategies Rewarded? An Analysis of Corporate Tax Avoidance - Eberhartinger, Eva; Safaei, Reyhaneh; Sureth-Sloane, Caren; Wu, Yuchen

Tax Complexity for Multinational Corporations in South Africa - Evidence from a Global Survey - Hoppe, Thomas; Safaei, Reyhaneh; Singleton, Amanda; Sureth-Sloane, Caren (Tax Simplification - An African Perspective)
This chapter examines the drivers of corporate income tax complexity for multinational corporations in South Africa. Based on unique data from a global survey of tax consultants which was conducted in 2016 by Hoppe et al, novel insights can be provided into the complexity of the South African tax system. The data enable a comparison of South Africa with the global mean of tax complexity, as well as with its major trade and investment partners. It is further possible to distinguish between different areas of tax complexity, ie, tax code complexity (complexity inherent in the different regulations of the tax code) and tax framework complexity (complexity that arises from the features and processes of a tax system). Frequent changes in tax regulations, ambiguity and interpretation, as well as record-keeping, are found to be the most important complexity drivers in the tax code of South Africa. The analysis further highlights that anti-avoidance provisions, such as transfer pricing and controlled foreign corporation rules, are perceived as most complex. With respect to tax framework complexity, the poor disclosure of audit selection criteria, the lack of experience or technical skills of tax officers in the audit process and problems associated with tax refunds appear to be serious concerns. Even though South Africa’s overall tax system complexity does not seem to differ very much from other related countries, a closer look into the details reveals a number of future challenges.